Preparation method and application of cerium-doped indium oxide evaporation target material

By doping cerium elements and adding carbon powder to the ICO evaporated target, the problems of insufficient strength and uneven pores of the target are solved, the resistivity and strength are improved, and the coating quality and production cost are optimized.

CN119774982AActive Publication Date: 2025-04-08ZHONGSHAN ZL ADVANCED MATERIALS TECHNOLOGY

Patent Information

Application Number
CN202411828511.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-08
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

During the preparation process of existing ICO evaporated targets, due to uneven pores, the target material has weak strength and is prone to powder loss, which affects the coating quality and production cost.

Method used

The resistivity of the target material is increased by doping cerium, and carbon powder is added during the mixing process to control the porosity and strength of the target material and optimize powder loss.

Benefits of technology

It improves the resistivity and strength of the target material, reduces powder loss, improves the uniformity and quality of the coating, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005184971480000111
    Figure BDA0005184971480000111
  • Figure BDA0005184971480000121
    Figure BDA0005184971480000121
Patent Text Reader

Abstract

The invention provides a preparation method and application of a cerium-doped indium oxide evaporation target material. Compared with the existing ITO target material for heterojunction and perovskite solar cells, the preparation method provided by the invention has the advantages that the resistivity of the target material is improved by doping the cerium element, and the relative density of the prepared target material is 59-64%. Meanwhile, the carbon powder is doped during mixing, so that the effects of controlling the porosity of the target material, improving the strength of the target material and optimizing the powder falling phenomenon of the target material are achieved. The invention also provides a transparent conductive oxide film containing the cerium-doped indium oxide evaporation target material and a photovoltaic solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnetron sputtering target material preparation, and specifically relates to a preparation method and application of a cerium-doped indium oxide evaporation target material. Background Art

[0002] In the current technological context, transparent conductive oxide (TCO) films have become a key material in the field of photovoltaic solar cells, especially in the production of high-efficiency solar cells. These films have received widespread attention because they can effectively collect photogenerated charges while allowing sunlight to pass through, thereby improving the efficiency of solar energy conversion. Among the many coating methods, reactive pulsed magnetron sputtering (RPD) has received special attention due to its unique advantages such as high deposition rate, better film quality, and higher target material utilization. In the field of photovoltaic solar cells, TCO films prepared by RPD can not only improve the photoelectric conversion efficiency of solar cells, but also reduce production costs, which is of great significance for achieving cost-effective solar cell products. Therefore, RPD technology shows broad application prospects in solar cell manufacturing and is one of the important directions for current and future research and development of solar cell technology.

[0003] Different from magnetron sputtering, the RPD process generally uses a target material with a porous structure with a relative density of about 60%. This is because during the RPD coating process, a target material with too high a density is prone to cracking, and a target material with too low a density is prone to splashing dust or structural collapse, making it impossible to obtain high-quality films.

[0004] Cerium-doped indium oxide (ICO) has more application advantages than ITO in photovoltaic cells due to its advantages such as ultra-high mobility and high film stability. Although ICO thin films have certain challenges in the complexity of the coating process, the excellent properties they show make it a direction worthy of further research and development. Compared with ITO targets, the ultra-high mobility of ICO targets provides a more ideal future for photovoltaic heterojunction cells and perovskite cells. However, the current preparation process of ICO evaporation targets has uneven porosity, which causes the target material itself to have weak strength, making the target material prone to a large amount of powder loss after sintering, causing chamber pollution during the coating process and increasing production costs. The film quality and uniformity are also difficult to control. Therefore, it is urgent to develop an ICO target preparation method that can improve the strength and porosity uniformity of the target material for evaporation. Summary of the invention

[0005] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the present invention provides a method for preparing a cerium-doped indium oxide evaporation target material. Compared with the existing ITO target material used for heterojunction and perovskite solar cells, the present invention improves the resistivity of the target material by doping cerium elements, and the relative density of the prepared target material is 59%-64%. At the same time, the present invention achieves the effect of controlling the porosity of the target material, improving the strength of the target material, and optimizing the powder loss phenomenon of the target material by doping carbon powder during mixing.

[0006] The invention also provides a cerium-doped indium oxide evaporation target material.

[0007] The invention also provides a transparent conductive oxide film.

[0008] The invention also provides a photovoltaic solar cell.

[0009] A first aspect of the present invention provides a method for preparing a cerium-doped indium oxide evaporation target, comprising the following steps:

[0010] S1: Mix nano cerium oxide powder and nano indium oxide powder and grind them by ball milling. After granulation, the materials are divided into two parts: material A1 and material B1;

[0011] S2: adding water to the material B1, and performing compression molding and granulation to obtain material B2;

[0012] S3: heating the material A1 and the material B2 to degrease, and then performing the first sintering on the material A1 and the material B2 after degreasing;

[0013] S4: ball milling the material A1 obtained after the first sintering to obtain material A2;

[0014] S5: dry-mixing the carbon powder with the material A2 to obtain material C, homogenously mixing the material C with the material B2 processed in step S3, adding water to the mixture, and hydraulically forming the mixture to obtain a target blank;

[0015] S6: sintering the target material blank to obtain a blank, and cutting and polishing the blank to obtain the cerium-doped indium oxide evaporation target.

[0016] A technical solution in the method for preparing a cerium-doped indium oxide evaporation target material of the present invention has at least the following beneficial effects:

[0017] Compared with the existing ITO target materials used in heterojunction and perovskite solar cells, the resistivity of the target material is increased by doping cerium, and the relative density of the prepared target material is 59%-64%. At the same time, the present invention achieves the effect of controlling the porosity of the target material, improving the strength of the target material, and optimizing the powder loss phenomenon of the target material by doping carbon powder during mixing.

[0018] The target material prepared by the present invention is applied to photovoltaic heterojunction cells and perovskite cells, is suitable for RPD coating, and can improve the conversion efficiency of the cells.

[0019] According to some embodiments of the present invention, in the preparation method of the present invention, the sum of the masses of nano-indium oxide powder, nano-cerium oxide powder and nano-carbon powder is 100%, wherein the mass of nano-indium oxide powder accounts for 94%-98%, the mass of nano-cerium oxide powder accounts for 1.5%-5%, and the mass of nano-carbon powder accounts for 0.5%-1%.

[0020] According to some embodiments of the present invention, in step S1, the D50 of the nano cerium oxide powder is 30-50 nm.

[0021] According to some embodiments of the present invention, the D50 of the nano indium oxide powder is 20-100 nm.

[0022] According to some embodiments of the present invention, in step S1, the mass ratio of material A1 to material B1 is 1:1 to 1.25.

[0023] According to some embodiments of the present invention, in step S3, the degreasing temperature is 600-650°C.

[0024] According to some embodiments of the present invention, the heating rate of the degreasing is 1.5°C / min-2°C / min.

[0025] According to some embodiments of the present invention, the degreasing insulation time is 2-3h.

[0026] According to some embodiments of the present invention, the first sintering step includes: raising the temperature to 850-900°C at 0.5-1.5°C / min, keeping warm for 3-4 hours, then raising the temperature to 1350-1450°C at 0.5-1°C / min, keeping warm for 3-10 hours, and then naturally cooling to room temperature.

[0027] According to some embodiments of the present invention, the first sintering step includes: increasing the temperature to 850-900°C at 1°C / min, keeping it for 3.5 hours, increasing the temperature to 1350-1450°C at 0.5°C / min, keeping it for 5 hours, and then naturally cooling to room temperature.

[0028] According to some embodiments of the present invention, in step S5, the molding pressure of the hydraulic molding is 10MPa-20MPa.

[0029] According to some embodiments of the present invention, in step S6, the step of sintering the green billet includes: heating the temperature to 600-650°C at a heating rate of 1.5°C / min-2°C / min for degreasing, keeping warm for 2-3 hours, heating the temperature to 850-900°C at a heating rate of 0.5-2°C / min, keeping warm for 3-4 hours, heating the temperature to 1400-1450°C at a heating rate of 0.5-1°C / min, keeping warm for 5-15 hours, and then naturally cooling to room temperature.

[0030] According to some embodiments of the present invention, in step S6, the diameter of the target material after cutting and polishing may be 30 mm, and the height may be 40 mm.

[0031] The second aspect of the present invention provides a cerium-doped indium oxide evaporation target material, which is prepared by the preparation method of the first aspect of the present invention.

[0032] One of the technical solutions of the present invention regarding the cerium-doped indium oxide evaporation target has at least the following beneficial effects:

[0033] Improve resistivity: Doping with cerium significantly increases the resistivity of the target material, which helps to optimize the electrical performance of photovoltaic cells.

[0034] Enhanced strength: By doping with carbon powder, the strength of the target material is improved, reducing the powder loss during use and increasing the service life of the target material.

[0035] Optimizing porosity: Regulating the porosity of the target material helps improve the uniformity and deposition quality of the material during the evaporation process, thereby improving the performance of photovoltaic devices.

[0036] Wide applicability: This target material is suitable for RPD coating and can be effectively used in photovoltaic heterojunction cells and perovskite cells to improve the conversion efficiency of the cells.

[0037] Simple and efficient preparation: Compared with traditional preparation methods, the method of the present invention simplifies the production process, improves the consistency and repeatability of the target material, and meets the requirements of industrial production.

[0038] Through these advantages, the target material of the present invention can exert greater performance improvement potential in the photovoltaic field.

[0039] The third aspect of the present invention provides a transparent conductive oxide film, which is prepared from the cerium-doped indium oxide evaporation target material of the second aspect of the present invention.

[0040] One of the technical solutions of the present invention regarding the transparent conductive oxide film has at least the following beneficial effects:

[0041] Excellent electrical conductivity: Cerium-doped targets improve the electrical conductivity of thin films and enhance their conductive properties in electronic devices.

[0042] High light transmittance: The film maintains good transparency and is suitable for use in optoelectronic applications such as solar cells and displays.

[0043] Thermal stability: Cerium doping enhances the thermal stability of the film, enabling it to maintain excellent performance under high temperature conditions.

[0044] Excellent mechanical properties: The strength and toughness of the film are improved, reducing peeling and damage during use.

[0045] Oxidation resistance: Cerium doping improves the corrosion resistance of the film, helping to extend its service life and stability.

[0046] A fourth aspect of the present invention provides a photovoltaic solar cell comprising the transparent conductive oxide thin film of the third aspect of the present invention.

[0047] One of the technical solutions of the present invention regarding photovoltaic solar cells has at least the following beneficial effects:

[0048] Improve conversion efficiency: Excellent conductivity and high light transmittance enhance the photoelectric conversion efficiency, making the battery more efficient in absorbing light energy.

[0049] Improved stability: The thermal stability and oxidation resistance of the film improve the reliability and durability of the battery under various environmental conditions.

[0050] Reduce weight: Transparent conductive films are usually lighter than traditional conductive materials, which helps to reduce the weight of the entire battery and facilitates installation and use.

[0051] Reduced costs: By optimizing material properties, it is possible to reduce the need for expensive materials, thereby reducing overall production costs.

[0052] Wide applicability: Suitable for various types of photovoltaic applications, such as heterojunction cells and perovskite cells, broadening the application range of batteries. DETAILED DESCRIPTION

[0053] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.

[0054] In a first aspect, some embodiments of the present invention provide a method for preparing a cerium-doped indium oxide evaporation target, comprising the following steps:

[0055] S1: Mix nano cerium oxide powder and nano indium oxide powder and grind them by ball milling. After granulation, the materials are divided into two parts: material A1 and material B1;

[0056] S2: adding water to material B1, and performing compression molding and granulation to obtain material B2;

[0057] S3: heating the material A1 and the material B2 to degrease, and then performing the first sintering on them respectively after degreasing;

[0058] S4: ball milling the material A1 obtained after the first sintering to obtain material A2;

[0059] S5: dry-mixing the carbon powder with the material A2 to obtain the material C, homogenously mixing the material C with the material B2 processed in step S3, adding water to the mixture, and hydraulically forming the mixture to obtain a target blank;

[0060] S6: Sintering the target blank to obtain a blank, and cutting and polishing the blank to obtain a cerium-doped indium oxide evaporation target.

[0061] It should be noted that, compared with the existing ITO target materials used for heterojunction and perovskite solar cells, the resistivity of the target material is increased by doping cerium, and the relative density of the prepared target material is 59%-64%. At the same time, the present invention achieves the effect of controlling the porosity of the target material, improving the strength of the target material, and optimizing the powder loss phenomenon of the target material by doping carbon powder during mixing.

[0062] The target material prepared by the present invention is applied to photovoltaic heterojunction cells and perovskite cells, is suitable for RPD coating, and can improve the conversion efficiency of the cells.

[0063] In combination with the first aspect, in some embodiments of the present invention, in the preparation method of the present invention, the mass proportion of nano indium oxide powder is 94%-98%, the mass proportion of nano cerium oxide powder is 1.5%-5%, and the mass proportion of nano carbon powder is 0.5%-1%.

[0064] It should be noted that in step S1, the material is divided into two parts, material A1 and material B1, after granulation, in order to obtain two powder precursors with different densities before the pre-sintering process. Material A1 is directly sintered without mold granulation, which is conducive to the subsequent ball milling to obtain powder particles with smaller particle size. Therefore, the material is first divided into two parts, material A1 and material B1 after granulation, water is added to material B1, and mold granulation is performed to obtain material B2, and then material A1 and material B2 are heated and degreased respectively. After degreasing, they are sintered for the first time respectively, and the material A1 obtained after the first sintering is ball milled to obtain material A2, which is conducive to obtaining powders of two particle sizes for mixing.

[0065] In combination with the first aspect, in some embodiments of the present invention, in step S1, the D50 of the nano-cerium oxide powder is 30-50 nm.

[0066] In combination with the first aspect, in some embodiments of the present invention, the D50 of the nano indium oxide powder is 20-100 nm.

[0067] In combination with the first aspect, in some embodiments of the present invention, in step S1, the mass ratio of material A1 to material B1 is 1:1 to 1.25.

[0068] In combination with the first aspect, in some embodiments of the present invention, in step S3, the degreasing temperature is 600-650°C.

[0069] In combination with the first aspect, in some embodiments of the present invention, the heating rate of the degreasing step is 1.5°C / min-2°C / min.

[0070] In combination with the first aspect, in some embodiments of the present invention, the holding time of the degreasing step is 2-3 hours.

[0071] In combination with the first aspect, in some embodiments of the present invention, the first sintering step includes: raising the temperature to 850-900°C at 1°C / min, keeping warm for 3.5 hours, then raising the temperature to 1350-1450°C at 0.5°C / min, keeping warm for 5 hours, and then naturally cooling to room temperature.

[0072] In combination with the first aspect, in some embodiments of the present invention, in step S5, the molding pressure of the hydraulic molding is 10MPa-20MPa.

[0073] In combination with the first aspect, in some embodiments of the present invention, in step S6, the step of sintering the green billet includes: heating to 600-650°C at a heating rate of 1.5°C / min-2°C / min for degreasing, keeping warm for 2-3 hours, heating to 850-900°C at 1°C / min, keeping warm for 3.5 hours, heating to 1400-1450°C at 0.5°C / min, keeping warm for 10 hours, and then naturally cooling to room temperature.

[0074] In combination with the first aspect, in some embodiments of the present invention, in step S6, the diameter of the target material after cutting and polishing may be 30 mm, and the height may be 40 mm.

[0075] In a second aspect, some embodiments of the present invention provide a cerium-doped indium oxide evaporation target, which is prepared by the preparation method of the first aspect of the present invention.

[0076] The cerium-doped indium oxide evaporation target material of the present invention, doped with cerium element, significantly improves the resistivity of the target material, which helps to optimize the electrical performance of photovoltaic cells. By doping with carbon powder, the strength of the target material is improved, the powder loss phenomenon during use is reduced, and the service life of the target material is increased. By regulating the porosity of the target material, it helps to improve the uniformity and deposition quality of the material during the evaporation process, thereby improving the performance of photovoltaic equipment. Furthermore, the target material is suitable for RPD coating, and can be effectively applied to photovoltaic heterojunction cells and perovskite cells to improve the conversion efficiency of the battery. Compared with traditional preparation methods, the method of the present invention simplifies the production process, improves the consistency and repeatability of the target material, and meets industrial production requirements. Through these advantages, the target material of the present invention can exert greater performance improvement potential in the photovoltaic field.

[0077] In a third aspect, in some embodiments of the present invention, a transparent conductive oxide film is provided, which is prepared from the cerium-doped indium oxide evaporation target material of the second aspect of the present invention.

[0078] The transparent conductive oxide film of the present invention, the target material doped with cerium improves the conductivity of the film and enhances its conductive performance in electronic devices. The film maintains good transparency and is suitable for use in optoelectronic applications such as solar cells and displays. Cerium doping enhances the thermal stability of the film, so that it can still maintain excellent performance under high temperature conditions. The strength and toughness of the film are improved, reducing peeling and damage during use. Cerium doping improves the corrosion resistance of the film, which helps to extend its service life and stability.

[0079] In a fourth aspect, in some embodiments of the present invention, a photovoltaic solar cell is provided, comprising the transparent conductive oxide thin film according to the third aspect of the present invention.

[0080] The photovoltaic solar cell of the present invention has excellent conductivity and high light transmittance, which enhances the photoelectric conversion efficiency and makes the battery more efficient in absorbing light energy. The thermal stability and oxidation resistance of the film improve the reliability and durability of the battery under various environmental conditions. Transparent conductive films are usually lighter than traditional conductive materials, which helps to reduce the weight of the entire battery and facilitate installation and use. Furthermore, by optimizing material properties, it is possible to reduce the demand for expensive materials, thereby reducing overall production costs. The photovoltaic solar cell of the present invention is suitable for various types of photovoltaic applications, such as heterojunction cells and perovskite cells, which broadens the application range of the battery.

[0081] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0082] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0083] Unless otherwise specified, "room temperature" in the present invention means 25°C±5°C.

[0084] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±2%.

[0085] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0086] Example 1

[0087] A cerium-doped indium oxide evaporation target was prepared, and the specific steps were as follows:

[0088] S1: Mix nano cerium oxide powder and nano indium oxide powder and grind them by ball milling. After granulation, the materials are divided into two parts: material A1 and material B1;

[0089] S2: adding water to the material B1, and performing compression molding and granulation to obtain material B2;

[0090] S3: heating the material A1 and the material B2 to degrease, and then performing the first sintering on the material A1 and the material B2 after degreasing;

[0091] S4: ball milling the material A1 obtained after the first sintering to obtain material A2;

[0092] S5: dry-mixing the carbon powder with the material A2 to obtain material C, homogenously mixing the material C with the material B2 processed in step S3, adding water to the mixture, and hydraulically forming the mixture to obtain a target blank;

[0093] S6: sintering the target material blank to obtain a blank, and cutting and polishing the blank to obtain the cerium-doped indium oxide evaporation target.

[0094] Among the preparation raw materials, the mass proportion of nano-indium oxide powder is 94%, the mass proportion of nano-cerium oxide powder is 5%, and the mass proportion of nano-carbon powder is 1%.

[0095] In step S1:

[0096] The D50 of nano cerium oxide powder is 40nm.

[0097] The D50 of nano indium oxide powder is 60nm.

[0098] The mass ratio of material A1 to material B1 is 1:1.

[0099] In step S3:

[0100] The degreasing temperature is 630°C.

[0101] The heating rate of degreasing is 2℃ / min.

[0102] The holding time for degreasing is 2h.

[0103] The first sintering step includes: increasing the temperature to 900°C at 1°C / min, keeping the temperature for 3.5 hours, increasing the temperature to 1400°C at 0.5°C / min, keeping the temperature for 5 hours, and then naturally cooling to room temperature.

[0104] In step S5:

[0105] The forming pressure of the hydraulic forming is 15MPa.

[0106] In step S6:

[0107] The steps of sintering the green billet include: heating to 650°C at a heating rate of 2°C / min for debinding, keeping warm for 2 hours, heating to 870°C at a heating rate of 1°C / min, keeping warm for 3.5 hours, heating to 1400°C at a heating rate of 0.5°C / min, keeping warm for 10 hours, and then naturally cooling to room temperature.

[0108] The target material after cutting and grinding has a diameter of 30 mm and a height of 40 mm.

[0109] Example 2

[0110] A cerium-doped indium oxide evaporation target was prepared. The difference from Example 1 is that in the preparation raw materials, the mass proportion of nano indium oxide powder is 95%, the mass proportion of nano cerium oxide powder is 4.25%, and the mass proportion of nano carbon powder is 0.75%.

[0111] Example 3

[0112] A cerium-doped indium oxide evaporation target was prepared. The difference from Example 1 is that in the preparation raw materials, the mass proportion of nano indium oxide powder is 96%, the mass proportion of nano cerium oxide powder is 3.5%, and the mass proportion of nano carbon powder is 0.5%.

[0113] Example 4

[0114] A cerium-doped indium oxide evaporation target was prepared. The difference from Example 1 is that in the preparation raw materials, the mass proportion of nano indium oxide powder is 97%, the mass proportion of nano cerium oxide powder is 2.5%, and the mass proportion of nano carbon powder is 0.5%.

[0115] Example 5

[0116] A cerium-doped indium oxide evaporation target was prepared. The difference from Example 1 is that in the preparation raw materials, the mass proportion of nano indium oxide powder is 98%, the mass proportion of nano cerium oxide powder is 1.5%, and the mass proportion of nano carbon powder is 0.5%.

[0117] Comparative Example 1

[0118] A cerium-doped indium oxide evaporation target was prepared. The difference from Example 1 is that no nano-carbon powder was added to the preparation raw materials, the mass proportion of nano-indium oxide powder was 96%, and the mass proportion of nano-cerium oxide powder was 4%.

[0119] Comparative Example 2

[0120] A cerium-doped indium oxide evaporation target was prepared. The difference from Example 1 is that in the preparation raw materials, the mass proportion of nano indium oxide powder is 94.5%, the mass proportion of nano cerium oxide powder is 3.5%, and the mass proportion of nano carbon powder is 2%.

[0121] Comparative Example 3

[0122] A cerium-doped indium oxide evaporation target was prepared. The difference from Example 1 is that in the preparation raw materials, the mass proportion of nano indium oxide powder is 90%, the mass proportion of nano cerium oxide powder is 9.5%, and the mass proportion of nano carbon powder is 0.5%.

[0123] Performance Testing

[0124] The powder loss, shrinkage, relative density and resistivity of the target materials prepared in the examples and comparative examples were tested. The results are shown in Table 1.

[0125] The test method for powder loss is: if there is powder residue after wiping the target surface with a dust-free cloth, the powder loss is more serious; if there is no powder residue on the surface without dust-free paper, it is mild.

[0126] The test method for shrinkage rate is: the volume of the target after sintering is divided by the volume before sintering.

[0127] The test method for relative density is the wax sealing method.

[0128] The test method for resistivity is: resistivity tester.

[0129] Table 1

[0130]

[0131]

[0132] In Example 1-5, the doping ratio of cerium oxide and carbon powder is adjusted compared with that in Comparative Example 1-3, wherein the mass proportion of indium oxide powder is 94%-98%, the mass proportion of nano-scale tungsten oxide powder is 1.5%-5%, and the mass proportion of nano-scale carbon powder is 0.5%-1%.

[0133] Carbon powder plays a role in controlling the porosity of the target material during the molding process, so that the molding strength can be greatly improved compared to when no carbon powder is added. During the sintering process, the carbon powder is converted into carbon dioxide under the action of high temperature and oxygen atmosphere, thereby achieving the effect of controllable target porosity. Finally, with the appropriate cerium oxide doping ratio, high-quality ICO targets for evaporation with high-strength surface and controllable relative density are finally sintered.

[0134] In Comparative Example 1, without adding carbon powder, the sintering shrinkage of the target material is too high and the relative density is too large, so it is not suitable for RPD coating.

[0135] In Comparative Example 2, the carbon powder doping ratio is too high, resulting in excessive porosity and too low relative density of the target after sintering, which ultimately causes the target to still suffer from severe powder shedding and is not suitable for RPD coating.

[0136] In comparative example 3, excessive doping of cerium oxide nanoparticles causes excessive lattice distortion, resulting in cracking of the target during sintering.

[0137] In Example 1-5, the shrinkage rate and relative density of the ICO target for evaporation are suitable by controlling the doping ratio. The sintered target is excellent in resistivity and target strength, and the processed evaporation target can be stably used for RPD coating.

[0138] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A method for preparing a cerium-doped indium oxide evaporation target, characterized in that: The following steps are involved: S1: mixing nano cerium oxide powder and nano indium oxide powder and ball milling, and then dividing the materials into two parts, material A1 and material B1 after granulation; S2: adding water to the material B1, and performing compression molding and granulation to obtain material B2; S3: heating the material A1 and the material B2 to degrease, and then performing the first sintering on the material A1 and the material B2 after degreasing; S4: ball milling the material A1 obtained after the first sintering to obtain material A2; S5: dry-mixing the carbon powder with the material A2 to obtain material C, homogenously mixing the material C with the material B2 processed in step S3, adding water to the mixture, and hydraulically forming the mixture to obtain a target blank; S6: sintering the target material blank to obtain a blank, and cutting and polishing the blank to obtain the cerium-doped indium oxide evaporation target.

2. The preparation method according to claim 1, characterized in that: Among the raw materials for preparation, the mass proportion of nano-indium oxide powder is 94%-98%, the mass proportion of nano-cerium oxide powder is 1.5%-5%, and the mass proportion of nano-carbon powder is 0.5%-1%.

3. The preparation method according to claim 1, characterized in that: In step S1, the D50 of the nano-cerium oxide powder is 30-50 nm; and / or the D50 of the nano-indium oxide powder is 20-100 nm.

4. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of material A1 to material B1 is 1:1 to 1.

25.

5. The preparation method according to claim 1, characterized in that: In step S3, the temperature of the degreasing is 600-650°C; and / or the heating rate of the degreasing is 1.5°C / min-2°C / min; and / or the holding time of the degreasing is 2-3h; And / or, the first sintering step includes: raising the temperature to 850-900°C at 0.5-1.5°C / min, keeping the temperature for 3-4 hours, raising the temperature to 1350-1450°C at 0.5-1°C / min, keeping the temperature for 3-10 hours, and then naturally cooling to room temperature.

6. The preparation method according to claim 1, characterized in that: In step S5, the molding pressure of the hydraulic molding is 10MPa-20MPa.

7. The preparation method according to claim 1, characterized in that: In step S6, the step of sintering the green billet includes: heating the temperature to 600-650°C at a heating rate of 1.5°C / min-2°C / min for degreasing, keeping the temperature for 2-3 hours, heating the temperature to 850-900°C at a heating rate of 0.5-2°C / min, keeping the temperature for 3-4 hours, heating the temperature to 1400-1450°C at a heating rate of 0.5-1°C / min, keeping the temperature for 5-15 hours, and then naturally cooling to room temperature.

8. A cerium-doped indium oxide evaporation target, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 7.

9. A transparent conductive oxide film, characterized in that: It is prepared from the cerium-doped indium oxide evaporation target material as described in claim 8.

10. A photovoltaic solar cell, characterized in that The transparent conductive oxide film according to claim 9 is included.

Citation Information

Patent Citations

  • Method for preparing carbon-doped TiO2 film by using two-step method

    CN104195520A

  • Indium tin cerium oxide target material and preparation method and application thereof

    CN116375463A

  • Preparation method of high-density cerium-doped indium oxide target material

    CN118771854A

  • Indium oxide-tin oxide powder and sputtering target using the same and method for producing the indium oxide-tin oxide powder

    CN1891663A

  • Indium oxide-tin oxide powder, sputtering target using it, and method of manufacturing indium oxide-tin oxide powder

    JP2007008752A

Cited By

  • Cerium-doped indium oxide-based evaporation target material as well as preparation method and application thereof

    CN121318386A

  • Gallium-cerium co-doped ITO target material and preparation method thereof

    CN121494528A